EFFECT OF COMPETENCE ON THE PERFORMANCE OF CIVIL SERVANTS IN THE OFFICE OF PUBLIC WORKS AND HOUSING MINISTRY OF THE CENTER OF SUMATRA RIVER REGION III PEKANBARU - Hendra, Teguh; Widyarini, Asri Mukti (Eko dan Bisnis: Riau Economic and Business Review, 2017)
Human resource issues in the spotlight as well as the foundation for the company to continue to survive. Human resources mempakan major role in every activity of the company. Although the number of facilities, infrastructure and resources, without the support of human resources activities of the company will not run properly. Thus mempakan human resources issues have to be considered in all his needs. Human resources will determine the successful implementation of the company's activities. For that in achieving organizational objectives required competence adequate human resources in driving performance and employee performance. The general objective of this research is separately the effect of competence on performance. The number of samples in this study as many as 52 people. The results in this study is competency has a positive and significant impact on the performance of employees at the Ministry of Public Works and Public Housing Hall of Sumatra River Region III pekanbaru. Test equipment used in this study using simple linear regression, t test, as well as to determine the influence of variables using the coefficient of determination. In a test of the validity of the entire item statement is valid for values obtained rhitung> rtabel (0.2732). Simple regression results obtained value Y = 21 524 + 0.611X. From the results of the partial test or t test was obtained tcount (5547)> t table (2.008) with a significant level of 0.000 <0.005, meaning that the variable competence positive and significant impact on performance variables. And the coefficient of determination R2 of 0.381, or 38.1%, meaning that the level of influence or contribution made by the competence variable to variable performance of 38.1% while the remaining 61.9% is influenced by other factors not examined in this study